Impact of the dimple indentation depth and location for passive flow control in Blended Wing Body airframe at low and high subsonic speeds - Haris Ali; Mohammad Rasidi Rasani; Zambri Harun (PLoS ONE, 2025)
This research investigates the role of dimples in enhancing the aerodynamic characteristics of a Blended-Wing-Body (BWB) airframe. Numerical simulations, grounded in Computational Fluid Dynamics (CFD), were utilized to model turbulent airflow and assess the aerodynamic forces acting on the wing structure. The k-ω Shear-Stress Transport (SST) turbulence model was applied to effectively solve the governing equations. The impact of four dimple indentation depths (d/Dd = 0.025, 0.05, 0.075, and 0.1) at six specific locations on either the suction or pressure sides of the BWB wing surface was investigated. Simulations were performed at Mach 0.15 and Mach 0.6, treating the flow as incompressible and compressible, respectively, to capture variations in aerodynamic behavior. The evaluation involved analyzing the drag coefficient (CD), lift coefficient (CL), and lift-to-drag (L/D) ratio. The results reveal that, under optimal conditions, a dimpled BWB surface can achieve a reduction in CD by as much as 4.09% relative to a non-modified surface, without negatively impacting lift. This improvement is primarily due to the dimples’ capacity to maintain attached flow and postpone flow separation. Implementing dimples on the BWB wing surface as a passive flow control method has proven effective in enhancing the aerodynamic efficiency of lifting surfaces.